2017
DOI: 10.3390/molecules22111956
|View full text |Cite
|
Sign up to set email alerts
|

Two Sulfur Glycoside Compounds Isolated from Lepidium apetalum Willd Protect NRK52e Cells against Hypertonic-Induced Adhesion and Inflammation by Suppressing the MAPK Signaling Pathway and RAAS

Abstract: Lepidium apetalum Willd has been used to reduce edema and promote urination. Cis-desulfoglucotropaeolin (cis-DG) and trans-desulfoglucotropaeolin (trans-DG) were isolated from Lepidium apetalum Willd, and caused a significant increase in cell viability in a hypertonic model in NRK52e cells. In the hypertonic model, cis-DG and trans-DG significantly promoted the cell viability of NRK52e cells and inhibited the elevation of Na+ in the supernatant, inhibited the renin-angiotensin-aldosterone (RAAS) system, signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…These cytokines are closely related to inflammation in many tissues. These inflammatory factors are important regulators of the renal inflammatory response and renal interstitial fibrosis (45). Our study also confirmed these findings.…”
Section: Discussionsupporting
confidence: 88%
“…These cytokines are closely related to inflammation in many tissues. These inflammatory factors are important regulators of the renal inflammatory response and renal interstitial fibrosis (45). Our study also confirmed these findings.…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, the MAPK signaling pathway is responsible for transmitting signals from the cellular membrane toward the nucleus in response to various stimuli. This pathway regulates a broader spectrum of cellular events such as growth, stress responses, and inflammation, thus, it is a broadly implicated therapeutic target for tumor and peripheral inflammatory conditions (Yuan et al, 2017). TNF is a well-known pleiotropic cytokine and has been demonstrated with several important roles in disease pathogenesis as well as homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…When the concentration of extracellular Na + is higher than that in the cell, the osmotic pressure increases, which leads to the cardiac myocyte enlargement and gradual apoptosis. 11 …”
Section: Resultsmentioning
confidence: 99%
“…When the concentration of extracellular Na + is higher than that in the cell, the osmotic pressure increases, which leads to the cardiac myocyte enlargement and gradual apoptosis. 11 The results showed that cell viability in the model group was significantly lower than that in the normal group (P<0.01). After the cells were treated with geniposide at different concentrations, their viability increased (P<0.01), and the most effective concentration of geniposide was determined to be 0.5 μmol/L.…”
Section: Detection Of Cell Viability By Mttmentioning
confidence: 88%